The billboard - Moore, Natalie Y. (Haymarket Books, 2022)
"The Billboard is about a fictional Black women's clinic in Chicago's Englewood neighborhood on the South Side and its fight with a local gadfly running for City Council who puts up a provocative billboard: "Abortion is genocide. The most dangerous place for a Black child is his mother's womb," spurring on the clinic to fight back with their own provocative sign: "Black women take care of their families by taking care of themselves. Abortion is self-care. #Trust Black Women." The book also has a foreword and afterword and QA with a founder of reproductive justice. As a play and book, The Billboard is a cultural force that treats abortion as more than pro-life or pro-choice."--Provided by publisher
Zusatz auf dem Cover: "a play about abortion"
Keywords: Schwangerschaftsabbruch; Abortion / Drama; Pro-life movement / Drama; Pro-choice movement / Drama; Women, Black / Drama; Abortion; Pro-choice movement; Pro-life movement; Drama; Théâtre; Theaterstück